2015
DOI: 10.1111/papr.12307
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management in Four‐Limb Amputation: A Case Report

Abstract: Acute pain following amputation can be challenging to treat due to multiple underlying mechanisms and variable clinical responses to treatment. Furthermore, poorly controlled preoperative pain is a risk factor for developing chronic pain. Evidence suggests that epidural analgesia and peripheral nerve blockade may decrease the severity of residual limb pain and the prevalence of phantom pain after lower extremity amputation. We present the perioperative analgesic management of a patient with gangrene of the bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A pre‐operative review of the literature demonstrated very few case reports of quadruple amputation [ 2 ] and those we found reported more limited amputations. Given the extent of the surgery planned and pre‐operative pain, we felt that nerve blockade would be important in minimising postoperative discomfort and the potential for development of chronic pain as well as maximising the potential for early rehabilitation.…”
Section: Discussionmentioning
confidence: 82%
“…A pre‐operative review of the literature demonstrated very few case reports of quadruple amputation [ 2 ] and those we found reported more limited amputations. Given the extent of the surgery planned and pre‐operative pain, we felt that nerve blockade would be important in minimising postoperative discomfort and the potential for development of chronic pain as well as maximising the potential for early rehabilitation.…”
Section: Discussionmentioning
confidence: 82%
“…Amputees are known to have various type of pain with different mechanisms of action, thus it is important to differentiate them, as they require distinctive modalities for management. Phantom Limb Pain (PLP), the sensation of pain in the amputated limb, and Residual Limb Pain (RLP), sensation of pain in the residual limb, are the two common clinical presentations of Post-operative pain [29]. Controlling pre-operative pain has been shown to decrease the likelihood of developing chronic pain [30].…”
Section: Other Principlesmentioning
confidence: 99%